Driving attention with the top down: the relative contribution of target templates to the linear separability effect in the size dimension. - Hodsoll, J; Humphreys, G; Humphreys, G (2001)
Bauer, Jolicoeur, and Cowan (1996a, 1996b, 1998) have shown that visual search for a target among distractors is apparently serial if the target is nonlinearly separable from the distractors in a particular feature space (e.g., color or size). In contrast, if the target is linearly separable from the distractors, search is relatively easy and seemingly spatially parallel. We examined the contribution of top-down knowledge of the target to the linear separability effect on search. Two visual search experiments were conducted using small, medium, or large circles as targets. In the first experiment, participants could use knowledge of the target to guide search, whereas, in the second, the target was unknown on each trial. Search for a medium (nonlinearly separable) target among small or large distractors benefited least from knowledge of the target as compared with search for a small or large target. Thus, the linear separability effect can be determined in part by use of top-down knowledge to facilitate the detection of targets at the ends of a continuum defining the stimuli.